Mga kagamitang panturo para sa paglinang ng mapanuring pagbasa sa mga mag-aaral na Tagalog sa ikaanim na baitang - Lumabas, Aurora C. 1946-
This study is an attempt to prepare instructional materials for developing critical reading skills. The researcher used documentary analysis, informal interviews, diagnostic test, questionnaire, and an analysis of the result of the assessment of the elementary education program in the Division of Bulacan. It was revealed that most of the grade six pupils were deficient in critical reading skills; most of the teachers in Pilipino do not provide enough lessons; and teachers do not integrate crucial topics. Based from the findings, the researcher recommended that seminars and work conferences be held often; a comprehensive list of objectives, lessons and activities be made available to teachers as references; more incentives in the form scholarships be given to teachers; and books and all other materials be revised or enriched so as to meet the present needs and demands.